Efficacy of fall-applied residual herbicides on weedy rice control in rice (Oryza sativa L.). (June 2019) - Bertucci, Matthew B.; Fogleman, Michael; Norsworthy, Jason K.
Abstract: Field experiments were initiated near Colt, AR, in the fall of 2016 and continued through the summer of 2018 to evaluate rice tolerance and weedy (or red) rice control after fall-applied very-long-chain fatty acid (VLCFA)-inhibiting herbicides. A split-plot design was used for the experiment, with the whole-plot factor being winter condition (flooded or non-flooded) and the split-plot factors being herbicide and rate. Herbicide treatments included acetochlor, dimethenamid-P, pethoxamid, pyroxasulfone, and S -metolachlor applied at 1, 050, 525, 420, 205, and 1, 070 g ai ha −1 and at 2, 100, 1, 050, 840, 410, and 2, 140 g ha −1 for low rates and high rates, respectively. Herbicides were applied in the fall, then 'CL172' rice was drill seeded in the spring of the following calendar year. Weedy rice control differed between years, but acetochlor and pyroxasulfone consistently provided the greatest levels of control across rates and flood conditions. Consequently, herbicides that best controlled weedy rice also caused the greatest injury to cultivated rice. Rice injury did not exceed 13% regardless of herbicide treatment at 3 wk after planting (WAP). However, the high rate of pyroxasulfone caused 20% rice injury at 5 WAP in 2018. Although it was expected that winter condition may affect residual activity of the VLCFA-inhibiting herbicides, herbicide selection and application rate both had much greater effects on rice injury and on weedy rice control. Based on these results, rice injury would be minimal or nonexistent after fall applications of the tested VLCFA inhibitors, and intermediate levels of weedy rice control may be achieved. The implementation of VLCFA-inhibiting herbicides in rice production systems would offer a novel herbicide site of action and offer a degree of selective control of weedy rice.